The methodological role of the hypothesis of God in the scientific researches of the 17th century - Otyutskiy, G.P. (Opción, 2019)
The article analyzes the methodological role of the concept of God in the natural science worldview of leading scholars and thinkers of the 17th century through comparative qualitative research methods. As a result, the concept of God is not only allows filling the existing gaps in the results of scientific knowledge but also itself acts as a kind of research tool since it allows treating natural phenomena as manifestations of God's functions. In conclusion, the hypothesis of God finally lost the status of the necessary methodological tool, which explains the specifics of many natural phenomena.